Cross-cultural comparison of Spanish and British "service-with-a-smile" outcomes. Issue 5 (4th July 2016) - Quinones, Cristina; Rodriguez-Carvajal, Raquel; Clarke, Nicholas; Griffiths, Mark D
Abstract : Purpose: – Employees working in the leisure service industry are required to show positive emotions when dealing with customers. However, empirical evidence confirms that faking emotions can lead to burnout. In contrast, employees that try to experience the emotions required by the role (i.e. deep acting (DA)) can lead to healthier outcomes. However, little is known about the process that underpins the link between DA and positive outcomes. Building on Côte's social interaction model of emotion regulation and evidence linking customer satisfaction and DA, it was hypothesized that DA would be associated with employees' self-actualization through customer interactions. This, in turn, was expected to explain the influence that DA has on relevant job attitudes (i.e. commitment, efficacy, turnover intentions). The model was tested in two countries with different emotional culture: Spain (i.e. impulsive) and the UK (i.e. institutional). Although UK was expected to report higher levels of effortful DA, the hypothesized process was expected to be the same. The paper aims to discuss these issues. Design/methodology/approach: – A cross-national design with theme park employees from Spain ( n =208) and UK ( n =204) was used. Hypotheses were tested with multigroup confirmatory factor analysis. Findings: – The relationship between job commitment and DA was mediated by self-actualization, and commitment partially explained the association between DA and professional efficacy in both countries. The impulsive-oriented country showed lower levels of DA and more positive job attitudes. Originality/value: – It is concluded that training employees to re-interpret costumer demands in less harming ways is required. The need to attend to cultural values is also discussed.